Carbon Nanotubes-Sponge Modified Electro Membrane Bioreactor (EMBR) and Their Prospects for Wastewater Treatment Applications - Ali M. Almusawy (Membranes, 2020)
A novel membrane bioreactor system utilizes Multi-Walled Carbon Nanotubes (MWCNTs) coated polyurethane sponge (PUs), an electrical field, and a nanocomposite membrane has been successfully designed to diminish membrane with fouling caused by activated sludge. The classical phase inversion was harnessed to prepare Zinc Oxide/Polyphenylsulfone (ZnO/PPSU) nanocomposite membranes using 1.5 g of ZnO nanoparticles (NPs). The prepared nanocomposite membrane surface was fully characterized by a series of experimental tools, e.g., Scanning electron microscope (SEM), Atomic force microscopy (AFM), contact angle (CA), pore size, and pore size distribution. The testing procedure was performed through an Activated Sludge-Membrane Bioreactor (ASMBR) as a reference and results were compared with those obtained with nanotubes coated sponge–MBR (NSMBR) and nanotubes coated sponge-MBR in the presence of an electrical field (ENSMBR) system. Observed fouling reduction of the membrane has improved significantly and, thus, the overall long-term was increased by 190% compared with the control ASMBR configuration. The experimental results showcased that sponge-carbon nanotubes (CNTs) were capable of adsorbing activated sludge and other contaminants to minimize the membrane fouling. At a dosage of 0.3 mg/mL CNT and 2 mg/mL of SDBS, the sponge-CNT was capable of eliminating nitrogen and phosphorus by 81% and >90%, respectively.